CAREER SELECTION OF PROFESSIONAL PUBLIC ACCOUNTANTS WITH EXPECTANCY THEORY - Indira Januarti; Anis Chariri (Jurnal Reviu Akuntansi dan Keuangan, 2019)
Abstract        This study aims to provide empirical evidence of the influence of intrinsic motivation (social values) and extrinsic (financial, professional training, work environment) selection of a career as a public accountant and non-CPAs. Similar research has been done but the respondent students majoring in accounting, so that the election is still a career intentions. This study uses respondents who had actually obtained the register of accountants so that their career choice becomes real not just intentions. The study sample as many as 251 graduates PPA Undip. Data obtained by sending a questionnaire via e-mail or via courier. The analytical tool used to test the hypothesis is logistic regression.The results of the study provide evidence that the only variable professional training has positive effects on the possibility of selecting a career as a public accountant and non-CPAs. Variable values of social, financial and environmental work is not a positive influence on elections for a career as a public accountant and non-CPAs. Financial variables and the working environment has a negative value, ie non public accounting profession provide financial expectations and working environment a better than the public accounting profession